SURVEY TERHADAP PERILAKU BELANJA ONLINE PENGGUNA SITUS JERAING SOSIAL DI JAKARTA - Yuliana Lisanti (Seminar Nasional Informatika (SEMNASIF), 2012)
Significant growth of Social networking users in Indonesia, 2nd highest in the world, has opened many opportunities to do business , which his online shopping, through this channel. Survey result in Jakarta, showed that more than 70% respondent had shopped online, at least one time, via social networking websites, and more than 90% of those buyer bought non digital product, although 60% respondent also said that many improvements are still needed when doing business through this new online channel. Key factors such as price, service and quality are some elements that could push or pull buyers to buy product or service. we need to understand these social networking online buyer’s behaviour, because it would open bigger opportunity so that business users could optimize their business via this new online channel. Qualitative reseatch method is used in this research , primary data were collected through questionnaire to some respondent in Jakarta, while secondary data were collected from previous research or other institutional survey result from various sources including internet.